Eight-hour medication-assisted treatment waiver training for opioid use disorder: integration into medical school curriculum. Issue 1 (1st January 2021) - Lien, Irvin C.; Seaton, Randell; Szpytman, Aaron; Chou, Jody; Webber, Victoria; Waineo, Eva; Levine, DianeL.
ABSTRACT: Background : The opioid epidemic is a growing problem in the USA. Use of medication-assisted treatment (MAT) has been effective in treating patients with opioid use disorders (OUD) and maintaining sobriety; however, there is a significant shortage of physicians formally trained in MAT. Objective : Wayne State University School of Medicine integrated the 8-hour MAT waiver training into its Internal Medicine clerkship curriculum. The objectives of integrating this into the curriculum were to (1) introduce opioid use education during students' Internal Medicine clerkship and (2) assess whether the curriculum prepares students to feel more comfortable evaluating and treating patients with OUD. Design : MAT training specifically for medical students was provided free online by the Providers Clinical Support System (PCSS). All students on the Internal Medicine clerkship were required to complete the training. A 7-question pre-survey and post-survey assessed students' comfort in evaluating and treating OUD. Significant changes were assessed with a paired McNemar Bowker Test. Results : Medical students (n = 141) completed the pre-survey and post-survey. After the MAT training, students' perspective of their clinical knowledge about OUD, familiarity with MAT, and likelihood to utilize MAT for their patients significantly differed, with increased proportions of medical students in agreement across 6 of 7 pre-post survey items ( p <.0001). Conclusions : Online MAT waiver training is a low-cost (free) way to introduce MAT education into the undergraduate clinical curriculum. Upon completing of the training, medical students self-reported improvements in their knowledge and attitudes about OUD and the different treatment options. Our hope is that MAT waiver training will allow for graduation of medical students who are ready to care for patients with OUD during residency and as practitioners upon completion of their residency.